Automatic Sex-Liking and Sex-Failure Associations in Men With Sexual Dysfunction. Issue 6 (24th July 2018) - van Lankveld, Jacques J. D. M.; de Jong, Peter J.; Henckens, Marcus J. M. J.; den Hollander, Philip; van den Hout, Anja J. H. C.; de Vries, Peter
Abstract : Current models of sexual functioning imply an important role for both automatic and controlled appraisals. Accordingly, it can be hypothesized that erectile dysfunction may be due to the automatic activation of negative appraisals at the prospect of sexual intercourse. However, previous research showed that men with sexual dysfunction exhibited relatively strong automatic sex-positive instead of sex-negative associations. This study tested the robustness of this unexpected finding and, additionally, examined the hypothesis that perhaps more specific sex-failure versus sex-success associations are relevant in explaining sexual dysfunction and distress. Male urological patients ( N = 70), varying in level of sexual functioning and distress, performed two Single-Target Implicit Association Tests (ST-IATs) to assess automatic associations of visual erotic stimuli with attributes representing affective valence ("liking"; positive versus negative) and sexual success versus sexual failure. Consistent with the earlier findings, the lower the scores on sexual functioning, the stronger the automatic sex-positive associations. This association was independent of explicit associations and most prominent in the younger age group. Automatic sex-positive and sex-failure associations showed independent relationships with sexual distress. The relationship between sexual distress and sex-failure associations is consistent with the view that automatic associations with failure may contribute to sexual distress.